Resilience and childhood trauma in a substance-dependent sample: A cross-sectional, controlled study. (3rd September 2022) - Aldemir, Ebru; Akyel, Betul; Havaceligi Atlam, Demet
ABSTRACT: Background: Childhood trauma has been regarded as a risk factor for substance use disorder and resilience has been found to be a protective factor against the development of psychopathology in the face of adversity. Methods: A total of 93 male substance-dependent patients and 59 healthy male volunteers were included. Resilience was assessed using the Resilience Scale for Adults, childhood trauma using the Childhood Trauma Questionnaire, and substance use with the Drug Use Disorders Identification Test. Results: Childhood trauma was higher, resilience was lower in the patient group. After controlling for any effects of age, education and severity of childhood trauma, regression results showed that for every one-point increase in resilience, there was a concomitant 15.78% decrease in severity of substance use disorder. Substance-dependent patients with a history of suicide attempt had lower resilience scores than substance-dependent patients without a history of suicide attempt. Conclusions: We conclude that resilience mitigates the severity of substance use disorder. Interventions to improve resilience might reduce the severity of substance use disorder and prevent suicide attempt in substance-dependent patients.